Gut microbes modulate bioaccessibility of lead in soil. (May 2021) - Bolan, Shiv; Seshadri, Balaji; Grainge, Ian; Talley, Nicholas J.; Naidu, Ravi
Abstract: Metabolic uptake of lead (Pb) is controlled by its bioaccessibility. Most studies have examined bioaccessibility of Pb in the absence of gut microbes, which play an important role in the metabolic uptake of nutrients and metal(loid)s in intestine. In this study, we examined the effect of three gut microbes, from various locations in the gut, on the bioaccessibility of soil ingested Pb. The gut microbes include Lactobacillus acidophilus, Lactobacillus rhamnosus and Escherichia coli . Lead toxicity to these three microbes was also examined at various pH values. Bioaccessibility of Pb was measured using gastric and intestinal extractions. Both Pb spiked and Pb-contaminated shooting range field soils were used to measure Pb bioaccessibility in the presence and absence of gut microbes. The results indicated that Pb toxicity to gut microbes, as measured by LD50 value, decreased with increasing pH, and was higher for Lactobacillus species. Gut microbes decreased the bioaccessible Pb; the effect was more pronounced at low pH, mimicking gastric conditions than in conditions closer to the intestine. Lead adsorption by these microbes increased at the higher pH tested, and E. coli adsorbed higher amounts of Pb than did the Lactobacillus species. The effect of gut microbes on reducing Pb bioaccessibility may be attributed to microbially-induced immobilization of Pb through adsorption, precipitation, and complexation reactions. The study demonstrates that bioaccessibility and subsequently bioavailability of metal(loid)s can be modulated by gut microbes, and it is important to undertake bioaccessibility measurements in the presence of gut microbes. Graphical abstract: Image 1 Highlights: One of the first studies on the role of gut microbes on bioaccessibility of Pb. Lead toxicity varied between gut microbes and was affected by the pH of growth medium. Gut microbes adsorbed a significant amount of Pb which also increased with pH. Gut microbes decreased both gastric and intestinal bioaccessibility of Pb. The decrease in bioaccessibility is attributed to microbial immobilization of Pb.